Decomposition of Fomes fomentatius fruiting bodies - transition of healthy living fungus into a decayed bacteria-rich habitat is primarily driven by Arthropoda - Bosch, Jason; Dobbler, Priscila Thiago; Větrovský, Tomáš; Tláskal, Vojtěch; Baldrian, Petr; Brabcová, Vendula (FEMS microbiology ecology, 2024)
Fomes fomentarius is a widespread, wood-rotting fungus of temperate, broadleaved forests. Although the fruiting bodies of F. fomentarius persist for multiple years, little is known about its associated microbiome or how these recalcitrant structures are ultimately decomposed. Here we used metagenomics and metatranscriptomics to analyse the microbial community associated with healthy living and decomposing F. fomentarius fruiting bodies to assess the functional potential of the fruiting body-associated microbiome and to determine the main players involved in fruiting body decomposition. F. fomentarius sequences in the metagenomes were replaced by bacterial sequences as the fruiting body decomposed. Most CAZymes expressed in decomposing fruiting bodies targeted components of the fungal cell wall with almost all chitin-targeting sequences, plus a high proportion of beta-glucan-targeting sequences, belonging to Arthropoda. We suggest that decomposing fruiting bodies of F. fomentarius represent a habitat rich in bacteria, while its decomposition is primarily driven by Arthropoda. Decomposing fruiting bodies thus represent a specific habitat supporting both microorganisms and microfauna.
Keywords: mikrobiota; temperate forest; Animals; Fomes fomentarius; Microbiota; deadwood fungi; členovci; plodnice hub; Coriolaceae; mycelium decomposition; Arthropods; Ascomycota; fruiting body; Bacteria; microbial communities; Fruiting Bodies, Fungal; zvířata